"No shit Sherlock"! Canine DNA and policing public space. Issue 3 (16th November 2020) - Langstone, Delia
Abstract : Purpose: This paper argues that this animal surveillance has the potential for considerable function creep going far outside the scheme's original objectives and acts as a conduit for more problematic surveillance of humans. This results in social sorting of people with subsequent unforeseen consequences leading to discrimination and curtailment of freedoms for both animals and their owners. Ultimately this opens people up to further intrusive targeting by commercial interests and, more alarmingly, scrutiny from law enforcement agencies. Design/methodology/approach: An empirical study examining an initiative involving the collection of canine DNA sources data from publicly available Cabinet, Select Committee and Scrutiny Committee records from the London Borough of Barking and Dagenham (LBBD). It also draws on news media sources, publicity material from the company running the scheme and from this and other local authorities. Methods include analysis of documents, semiotic and discourse analysis. Findings: This paper highlights the importance of animals to surveillance studies and examines the extent to which animals are a part of the surveillant assemblage in their own right. It also demonstrates how nonhuman animals extend the reach of the surveillant assemblage. Social implications: The scheme was called a badge of considerate dog ownership, yet it is one that can be franchised to tie up with diverse income streams being described as advantageous in the age of austerity. In 2017, it was reported that this scheme was to be rolled out in other areas and was moving from being voluntary to being mandatory with the enforcement of Public Space Protection Orders (PSPOs). These have been described as "geographically defined ASBOS" that have come into force under the Anti-social Behaviour and Policing Act (2014); they often work to criminalise activities that were not previously considered illegal. Originality/value: In the theorising of surveillance, animals have been largely overlooked. Epidemiological studies proliferate, yet the role of animals in many aspects of everyday surveillance has been neglected.